The Effect of Classical Music Therapy on Pain and Anxiety in Hypertensive Patients at Otanaha Hospital - Mutia; Muhammad Isman Jusuf; Gusti Pandi Liputo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Hypertension can be a serious threat to society because it can increase the risk of heart disease, stroke and other health problems. The treatment is carried out with non-pharmacology, namely listening to music, one of which is classical music. This study aims to determine the effect of classical music therapy on pain and anxiety in Hypertension patients at Otanaha Hospital. The research method uses pre-experimental with one group pre-test and post-test design approaches. The population of this study is hypertension patients who are in Otanaha Hospital in internal room 2. The number of samples in this study amounted to 50 respondents using a nonprobability sampling technique in the form of accidental sampling. The results showed that pain before being given music therapy was in the moderate category as many as 24 respondents (48%), heavy as many as 5 respondents (10%). After being given music therapy, which was moderate as many as 15 respondents (30%), light as many as 30 respondents (70%). Anxiety before being given music therapy was in the severe category of 7 respondents (14%), very severe as many as 43 respondents (86%). After being given music therapy, it was moderate as many as 45 respondents (90%), light as many as 5 respondents (10%). The results of the statistical test were obtained that there was an effect of classical music therapy on pain and anxiety in hypertensive patients at Otanaha Hospital using the Wilcoxon test for pain and anxiety using the Paired T-test with a p value of 0.000 (<0.05). Conclusion: the application of classical music therapy is able to reduce pain and anxiety in hypertensive patients. For people with hypertension, apply classical music therapy by modifying the environment that will be used so that the atmosphere is calm.